Phylogenetic and morphological study of the genus Potamolithus (Truncatelloidea: Tateidae) in hotspots of diversity at the Paranaense Forest, Argentina, with the addition of six new species - de Lucía, Micaela (2021)
The Atlantic Forest is a highly fragmented biodiversity hotspot, which in Argentina is represented by the Paranaense Forest, covering a wide area of the province of Misiones. In conservation studies, groups of vertebrates, plants and arthropods are generally used together but other invertebrates scarcely used. In the present work, we aim to provide information on new species of freshwater gastropods, from protected and unprotected areas. Specimens were collected in a protected area (Yabotí Biosphere Reserve) and in two unprotected areas (Alba Posse city and Centro de Investigaciones Antonia Ramos -CIAR-). The shell, radula, internal anatomy and the molecular information of the partial sequence of mitochondrial cytochrome c oxidase subunit I (COI) were analysed. The phylogenetic trees were obtained using Maximum Likelihood and Bayesian Inference analyses. Altogether, the anatomical, shell, and genetic studies allow us to differentiate six new species of the genus Potamolithus from the others present in Argentina and the surrounding areas. These new species raise the number of freshwater gastropods for the malacological province Río Uruguay to 64. Three of the new species have been found within a protected area, while other three at unprotected areas. The presence of invasive species, such as Limnoperna fortunei (Dunker 1857) and Melanoides tuberculata (Müller, 1774), as well as the possible creation of a hydroelectric dam, may modify the environment inhabited by the new endemic fauna.